Analisis Strategi Pemberdayaan Kelompok Wanita Tani Hijau Lestari Dusun II Desa Jati Kesuma Kecamatan Namorambe Kabupaten Deli Serdang - Tri Ananda; Jubaidah Hasibuan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the strategy of women's empowerment through the Hijau Lestari Women Farmers Group (KWT) in Jati Kesuma Village, and to analyze how the empowerment process takes place through various group activities. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research informants include the Head of the Agricultural Technical Implementation Unit (UPT), the Village Head, the Chairperson of the Women Farmers Group, and group members. The results of the study indicate that women's empowerment is implemented through five main strategies, namely motivational strategies, awareness-raising strategies, self-management strategies, resource mobilization strategies, and network building strategies. Motivational strategies increase women's self-confidence to participate actively; awareness strategies help women understand their roles in agriculture; self-management strategies strengthen women's ability to manage time and make decisions; resource mobilization strategies provide access to agricultural facilities and technical guidance; and network building strategies expand group relationships with the village government, UPT Agriculture, and the surrounding community. All of these strategies have been proven to produce positive changes in improving women's skills, knowledge, solidarity, and economic independence. This study concluded that women's empowerment through the Hijau Lestari Women Farmers Group (KWT) is effective and has had a positive impact on improving women's skills, self-confidence, and economic contribution. This program also strengthens collaboration, increases insight, and encourages women's active participation in village development.